The Role of Corporate Social Responsibility in Driving Consumer Loyalty and Brand Equity (Journal of Advances and Scholarly Researches in Allied Education, 2025)
As a necessary connotation of long-term business investment and competitive advantage, Corporate Social Responsibility (CSR) has spawned its own history; one that dates back thousands of years. People are now more aware than ever before about ethical, social and environmental issues. CSR initiatives put people at ease and win trust for brands. Against this backdrop, globalization has generated novel challenges for nation states and non-governmental organizations alike. This research examines the role of CSR in shaping a consumer’s perception of the brand, the level of trust he assigns to that brand, and his resulting commitment to it (all of which serve as precursors to consumer loyalty). Carroll’s Corporate Social Responsibility Pyramid and Aaker’s Brand Equity model are used to provide the necessary theoretical framework and value to this study. We use a mixed-methods research design in which we analyse secondary data from well-known businesses such as Tata, Infosys, Unilever and Starbucks, and also survey 250 consumers .Quantitative analysis tools were then employed to investigate the relationship between corporate social responsibility engagement and customer loyalty: regression analysis tested the model fit while correlation tests were carried out to examine relationships between different variables. The deeper understanding of context offered by qualitative research similarly helped make sense out the statistical findings we had uncovered. These show that the impact of any social responsibilities carried out by companies is felt in consumer trust, happiness and their attachment to a brand – all of which in turn increase general brand equity. Further, the results make it absolutely clear that companies with a reputation for social responsibility can achieve higher consumer retention rates, more powerful word-of-mouth promotion and are able generally to hold onto market value. As such, we conclude by proposing key strategies for companies seeking to incorporate CSR initiatives as an integral part of their business, while indicating both the theoretical and practical significance of our findings for researchers.